The Role of Corporate Entrepreneurship in The Relationship Between Entrepreneurial Leadership and Corporate Culture to Corporate Performance at PT. AS - Soenardi, Eny (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Technological disruption in this digitalization era has brought technological advances and changes in trends that are quite large and affected in a decline in corporate performance. This study aims to determine the role of corporate entrepreneurship in the relationship between entrepreneurial leadership and corporate culture towards increasing corporate performance. The variables studied are entrepreneurial leadership (X 1), corporate culture (X2), corporate entrepreneurship (Y), and corporate performance (Z). The population in this study is all paper mill employee of PT. AS with job level assistant supervisor to general manager. The sample consists of 76 respondents determined using saturated sampling method. Researcher used a statistical analysis model of Structural Equation Modeling (SEM) and use Partial Least Square (PLS) for analysis tools. Results show that entrepreneurial leadership has an effect on corporate cntreprenurship, corporate culture has an effect on corporate entreprenurship, corporate entrepreneurship has an effect on corporate performance, entrepreneurial leadership has no effect on corporate performance, and corporate culture has not effect on corporate performance at PT. AS.